Data Supporting "A comprehensive CFD investigation of tip vortex trajectory in shrouded wind turbines using compressible RANS solver" - Silva, Paulo (Cranfield University, 2024)
This dataset support the publication "A comprehensive CFD investigation of tip vortex trajectory in shrouded wind turbines using compressible RANS solver" it contains mesh, isosurface and additional data
Keywords: CFD'; 'Wind Turbines'; 'Vortex'; 'Diffuser Augmented Wind turbines'; 'Diffuser'